PUBLIC HEALTH INNOVATIONS FOR ACCELERATING STUNTING REDUCTION: EVIDENCE FROM BANGGAI LAUT, INDONESIA - Haeruddin Haeruddin; Reza Aril Akhri; Wardia Hamzah; Nur Azizah A. Radjulaeni (International Archives of Medical Sciences and Public Health, 2026)
This study analyzed three innovations that successfully reduced stunting prevalence within one year. A qualitative phenomenological approach was used to explore the implementation of these innovations. Informants included health workers, Dukcapil officers, community leaders, and community members involved in the programs. Findings showed that the Dukcapil Menyapa innovation improved data availability, mapping, and continuous monitoring, enabling early and targeted interventions from pregnancy to early childhood. The Kanjoli-an Prima innovation provided specialist visits every seven days, integrated with health education, direct healthcare services, and community assistance. Meanwhile, the Coriander innovation focused on intensive monitoring and support for pregnant women from early pregnancy until childbirth. Overall, an integrated, innovation-based, and cross-sectoral approach supports accelerating stunting reduction. These innovations demonstrate strong public health relevance and scalability potential for implementation in regions with similar socio-demographic conditions, although further mixed-methods studies are needed to assess long-term effectiveness and sustainability